Efficacy and toxicity outcomes for patients treated with focal salvage high dose rate brachytherapy for locally recurrent prostate cancer. (July 2020) - Slevin, Finbar; Hodgson, Samantha; Rodda, Sree Lakshmi; Bownes, Peter; Bottomley, David; Adiotomre, Ese; Al-Qaisieh, Bashar; Dugdale, Emma; Hulson, Oliver; Mason, Joshua; Smith, Jonathan; Henry, Ann M.
Highlights: Local recurrence of prostate cancer may be treated with salvage therapies. Focal salvage high dose rate brachytherapy provides good biochemical control. Severe genitourinary and gastrointestinal toxicities are low. Abstract: Introduction: Isolated local recurrence of prostate cancer following primary radiotherapy or brachytherapy may be treated with focal salvage high dose rate brachytherapy, although there remains an absence of high quality evidence to support this approach. Methods: Men with prostate cancer treated consecutively between 2015 and 2018 using 19 Gy in a single fraction high dose rate brachytherapy (HDR) for locally recurrent prostate cancer were identified from an institutional database. Univariable analysis was performed to evaluate the relationship between patient, disease and treatment factors with biochemical progression free survival (bPFS). Results: 43 patients were eligible for evaluation. Median follow up duration was 26 months (range 1–60). Median bPFS was 35 months (95% confidence interval 25.6–44.4). Kaplan-Meier estimates for bPFS at 1, 2 and 3 years post salvage were 95.2%, 70.6% and 41.8% respectively. On univariable Cox regression analysis, only nadir PSA was significantly associated with bPFS although the majority of patients were also treated with androgen deprivation therapy. Only one late grade 3 genitourinary toxicity was observed. Conclusion: Focal salvage HDR brachytherapy may provide good biochemical control with a low risk of severe toxicity. Further evaluation within clinical trials are needed to establish its role in the management of locally recurrent prostate cancer.